2020
DOI: 10.3390/ijerph17144988
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Spatiotemporal Pattern of Depressive Symptoms Caused by COVID-19 Using Social Media Data Mining

Abstract: By 29 May 2020, the coronavirus disease (COVID-19) caused by SARS-CoV-2 had spread to 188 countries, infecting more than 5.9 million people, and causing 361,249 deaths. Governments issued travel restrictions, gatherings of institutions were cancelled, and citizens were ordered to socially distance themselves in an effort to limit the spread of the virus. Fear of being infected by the virus and panic over job losses and missed education opportunities have increased people’s stress levels. Psychological studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 44 publications
(45 reference statements)
4
46
0
2
Order By: Relevance
“…Overall, these correlations may demonstrate our questionnaire’s sensitivity in capturing stress-related effects of COVID-19 in real-time. Interestingly, a similar correlation between stress symptoms (assessed by social media data mining) and the number of new COVID-19 cases was also found in a study in the United States 16 .…”
Section: Resultssupporting
confidence: 76%
“…Overall, these correlations may demonstrate our questionnaire’s sensitivity in capturing stress-related effects of COVID-19 in real-time. Interestingly, a similar correlation between stress symptoms (assessed by social media data mining) and the number of new COVID-19 cases was also found in a study in the United States 16 .…”
Section: Resultssupporting
confidence: 76%
“…Additionally, they analyzed the time and location for the geotagged tweets (in our work, we use multiple methods for the location extraction of tweets). Li et al [ 61 ] detected stress symptoms related to COVID-19 in the United States. They integrated a Correlation Explanation (CorEx) learning algorithm and clinical Patient Health Questionnaire (PHQ) lexicon and proposed a CorExQ9 algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results revealed that anti-vaccination users on Twitter became highly entangled with undecided users in the main online network, whereas pro-vaccination users are more peripheral in the network. Li et al [ 39 ] applied machine learning techniques to detect stress symptoms-related tweets on Twitter and manifested that people’s stress symptoms expressed on Twitter have a strong correlation with increasing cases. They also discovered that the main stressors switched from concerns on the increase of reported deaths to financial burdens and economic downturns.…”
Section: Literature Reviewmentioning
confidence: 99%